Newspapers in Science Education: A Study Involving Sixth Grade Students - Ching-san Lai; Yun-Fei Wang (Journal of Education in Science, Environment and Health)
The purpose of this study was to explore the learning performance of sixth grade elementary school students using newspapers in science teaching. A quasi-experimental design with a single group was used in this study. Thirty-three sixth grade elementary school students participated in this study. The research instruments consisted of three questionnaires, a “Learning Attitude toward Newspapers in Education Scale” (29 items, Cronbach’s α = .90), a “Science Reading Attitude Scale” (15 items, Cronbach’s α = .93), and an “Attitude toward Science Scale” (27 items, Cronbach’s α = .92). All three questionnaires have good reliabilities. Furthermore, the validity of these questionnaires has been confirmed by three science educators. The results showed that the use of newspapers in education and multiple instructional strategies can (1) effectively enhance the sixth graders’ learning attitudes towards the use of newspapers in science education and enhance their reading of science articles and involvement in science experiments; (2) effectively promote the sixth graders’ attitudes toward science reading and enhance their science reading understanding; and (3) enhance the sixth graders’ performance in scientific attitudes and significantly strengthen their science learning and interest. The research results showed that the use of newspapers in science teaching effectively enhances the science learning performance of the sixth grade students.